Law Enforcement against the Crime of Threatening in Paguyaman Pantai Sub-District - Niuwa, Riyan (Estudiante Law Journal, 2024)
The purpose of this study is to understand how law enforcement against criminal acts of threatening in the coastal paguyaman sub-district. The research method used in this research is empirical research method using qualitative method, an approach that produces information in the form of information, described in writing, and associated with other data to obtain a more comprehensive understanding of the reality that occurs. The results of this research show that not all cases of criminal threats can be resolved through mediation; selection of cases to be handled needs to be done. Police at Paguyaman Pantai Police Station first evaluate the impact on the victim of the case. If the case is considered minor and can be mediated, the police will try to resolve it through mediation. However, cases involving repeat offenders are not suitable for mediation. Mediation also depends on the willingness of the victim, as the final decision remains with the victim, while the police can only try to encourage it. In this case, the police use their discretion to facilitate penal mediation, acting as a mediator between the two parties. When the victim and the offender agree to mediation, the role of the police as mediator is to connect them and help formulate goals so that an agreement can be reached.